Modern theories of art. - Barasch, Moshe (New York University Press, 1998)
In this volume, the third in his classic series of texts surveying the history of art theory, Moshe Barasch traces the hidden patterns and interlocking themes in the study of art, from Impressionism to Abstract Art. Barasch details the immense social changes in the creation, presentation, and reception of art which have set the history of art theory on a vertiginous new course: the decreased relevance of workshops and art schools; the replacement of the treatise by the critical review; and the interrelation of new modes of scientific inquiry with artistic theory and praxis. The consequent changes in the ways in which critics as well as artists conceptualized paintings and sculptures were radical, marked by an obsession with intense, immediate sensory experiences, psychological reflection on the effects of art, and a magnetic pull to the exotic and alien, making for the most exciting and fertile period in the history of art criticism.